2024
DOI: 10.3390/w16071001
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining the Pearl River: A Critical Review of Changes in Fluvial Geomorphological Processes and the Driving Forces in the Pearl River Basin

Haidong Ou,
Shirong Cai,
Wei Fan
et al.

Abstract: The Pearl River is one of China’s large rivers, the second-largest river and the fourth-longest river in China. Its unique geography, landform, and climate conditions create unique fluvial geomorphological processes. Affected by human activities and climate change, the fluvial geomorphological processes in the Pearl River Basin have undergone significant changes in recent decades, seriously affecting the river’s sustainable development. This paper critically reviews changes in fluvial geomorphological processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 114 publications
1
0
0
Order By: Relevance
“…reductions in cropland are observed to gradually weaken from developed regions to rural ones [53]. This study found that the decline in grassland primarily occurred in the northwestern PPRB, while the decrease in cropland was mainly observed in the central region as well as the coastal and Pearl River Delta areas, which is consistent with the findings of Ou et al [54]. Land management policies are also crucial driving forces for land use changes in the PPRB [55].…”
Section: Drivers Of Land Use Changesupporting
confidence: 90%
“…reductions in cropland are observed to gradually weaken from developed regions to rural ones [53]. This study found that the decline in grassland primarily occurred in the northwestern PPRB, while the decrease in cropland was mainly observed in the central region as well as the coastal and Pearl River Delta areas, which is consistent with the findings of Ou et al [54]. Land management policies are also crucial driving forces for land use changes in the PPRB [55].…”
Section: Drivers Of Land Use Changesupporting
confidence: 90%